Brazil's Growth Performance: A Comparative Perspective to the Asian Giants - Nazmi, Nader; Revilla, Julio E. (2012)
We compare economic efficiencies in Brazil, India, and China, where economic efficiency measures the gap between potential and actual output for a given input combination and technological factor. We use stochastic production frontier models to measure the contributions of factors of production and technology to growth and estimate non-positive error terms that capture production inefficiencies in each country. The results suggest that China and India had relatively inefficient production in the early 1980s but have since improved production efficiency substantially. In the same period, production efficiency in Brazil has lagged those of China and India. The gap between Brazil's production efficiency and those of its Asian peers has narrowed in recent years. However, production remains more efficient in China and India, supporting more rapid growth in these countries relative to Brazil.